Pengembangan Alat Permainan Edukatif Stik Hitung untuk Mengembangkan Kemampuan Kognitif Peserta Didik di TK Kartini Kabupaten Majene - Nurhalisa, Nurhalisa; Sulaiman, Umar; Agusriani, Ade (NANAEKE: Indonesian Journal of Early Childhood Education, 2025)
This study aims to develop an Educational Game Tool (APE) called “Stik Hitung” (Situng) that is suitable for use in early childhood learning and meets the criteria of validity, practicality, and effectiveness. The APE Situng was designed to support the learning process and enhance cognitive abilities, particularly symbolic thinking skills. This research employed the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects included two validator lecturers from the State Islamic University of Makassar and one teacher from TK Kartini, Lembang Village, Majene Regency. The validation results showed that APE Situng achieved an average score of 90.3%, categorized as highly valid. The practicality test conducted with 15 students obtained a score of 87.5%, categorized as highly practical, while the effectiveness test indicated an increase in scores from 54.33 (pretest) to 87.33 (posttest), categorized as very good and exceeding the minimum competency standard. These results confirm that APE Situng is feasible and effective as a learning medium to improve the cognitive abilities of young children. The implication is that concrete, play-based learning media such as APE Situng can serve as an innovative alternative to enhance symbolic thinking skills in early childhood education.